2013 IEEE 26th International Conference on Micro Electro Mechanical Systems (MEMS) 2013
DOI: 10.1109/memsys.2013.6474273
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and fabrication of zinc oxide nanowire devices

Abstract: In this paper, we demonstrate an approach for the local synthesis of ZnO nanowires (ZnO NWs) and the potential for such structures to be incorporated into device applications. Three network ZnO NW devices are fabricated on a chip by using a bottom-up synthesis approach.Microheaters (defined by standard semiconductor processing) are used to synthesize the ZnO NWs under a zinc nitrate (Zn(NO 3 ) 2 ·6H 2 O) and hexamethylenetetramine (HMTA, (CH 2 ) 6 ·N 4 ) solution. By controlling synthesis parameters, varying d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…65 It has later been found that Si3N4 shows better constraint on vertical nanowire growth than SiO2, and thus a better integrated design has been achieved using Si 3 N 4 . 66 Udrea et al have carried out hydrothermal growth on silicon-on-insulator (SOI) based CMOS pz silicon micro-heaters. After foundry fabrication of SOI…”
Section: Cmos Integrated Nanowire Growthmentioning
confidence: 99%
“…65 It has later been found that Si3N4 shows better constraint on vertical nanowire growth than SiO2, and thus a better integrated design has been achieved using Si 3 N 4 . 66 Udrea et al have carried out hydrothermal growth on silicon-on-insulator (SOI) based CMOS pz silicon micro-heaters. After foundry fabrication of SOI…”
Section: Cmos Integrated Nanowire Growthmentioning
confidence: 99%